2017
DOI: 10.1177/0973258617743618
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Empowerment and Exploitation: Virtual Ethnography on Internet Immaterial Labour in Macao

Abstract: Recently, the research topic of immaterial labour had become one of the most significant discussions about the changing nature of capitalism. But the previous studies mainly regard immaterial labour as a unidirectional process of capitalist exploitation in abstract sense, rather than a paradoxical dynamics of exploitation and empowerment in specific context. This article, therefore, investigates immaterial labour in digital capitalism, with a specific case study of the local practices of Internet immaterial la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The other major line of thinking points to the empowering potential of prosumption (Bucher and Fieseler, 2017; Jin and Feenberg, 2015; Zhongxuan, 2018). From this standpoint, understanding of prosumption cannot be simply reduced to its economic functions.…”
Section: Social Media Prosumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other major line of thinking points to the empowering potential of prosumption (Bucher and Fieseler, 2017; Jin and Feenberg, 2015; Zhongxuan, 2018). From this standpoint, understanding of prosumption cannot be simply reduced to its economic functions.…”
Section: Social Media Prosumptionmentioning
confidence: 99%
“…From this standpoint, understanding of prosumption cannot be simply reduced to its economic functions. Although non-monetary, users do gain various benefits from prosumption, such as enjoyment, satisfaction, social connectedness, criticisms of established institutions, and participation in civic life (Bucher and Fieseler, 2017; Weeks et al, 2017; Zhongxuan, 2018). For example, Weeks et al (2017) found that prosumers who actively consumed news, expressed political opinions, and produced political content were more likely to persuade others to be politically active than non-prosumers.…”
Section: Social Media Prosumptionmentioning
confidence: 99%
“…Virtual ethnography is applied in exploring the internet and observing the users, in this case, is Instagram. The aim of elaborating ethnography and the internet is to investigate how the status of the internet is negotiated with the local context of its user (Hine in Zhongxuan, 2018). This shows the communication which is seen through the internet.…”
Section: Methodsmentioning
confidence: 99%
“…Other research papers have pinpointed the influence that other media have on the viewing of this type of content (Burkey, 2019; Zhongxuan, 2017). Cantero de Julián et al (2020), for example, analysed the production of 360 videos by Spanish TV channels, concluding that their presence in social networks is less than relevant.…”
Section: Literature Review: Facebook and Youtubementioning
confidence: 99%